(untitled) (Global Journal of Computer Science and Technology, 2023)
A database management system is frequently used by users to handle data protection which is at the core of many security systems The security of database management systems is the main topic of this essay which serves as an illustration of how application security may be planned and implemented for certain tasks Due to the fact that databases are more recent than programming languages and operating systems there is currently a lot of interest in DBMS Security Many commercial and governmental organizations depend on databases because they store data in a way that makes retrieving and maintaining it simple and effective Because databases are a favorite target for attackers their structure and contents are regarded as significant company assets that must be carefully protected Similar to other computing systems databases have some fundamental security requirements Access control excluding erroneous data user authentication and reliability are the main issues The problems and dangers to database security are discussed in this paper